2012
DOI: 10.1016/j.jacc.2012.03.059
|View full text |Cite
|
Sign up to set email alerts
|

Differential Response to Cardiac Resynchronization Therapy and Clinical Outcomes According to QRS Morphology and QRS Duration

Abstract: QRS morphology is a more important baseline electrocardiographic determinant of CRT response than QRSd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
64
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 93 publications
(68 citation statements)
references
References 19 publications
(18 reference statements)
2
64
1
1
Order By: Relevance
“…The aforementioned separate analyses showing that QRS duration and morphology are important determinants of clinical benefits of CRT have led to the investigation of the interaction between QRS duration and morphology and its effects on CRT outcomes 5, 10, 23, 24. The sub‐analysis of the RAFT trial (after excluding patients with ventricular pacing and permanent atrial fibrillation) showed that regardless the QRS duration, patients with LBBB morphology who were randomized to CRT with defibrillator function showed a reduction in the rates of the primary outcome (composite endpoint of all‐cause mortality and heart failure hospitalization) (HR 0.640; 95% CI 0.524–0.781; P  < 0.001) 5.…”
Section: Discussionmentioning
confidence: 99%
“…The aforementioned separate analyses showing that QRS duration and morphology are important determinants of clinical benefits of CRT have led to the investigation of the interaction between QRS duration and morphology and its effects on CRT outcomes 5, 10, 23, 24. The sub‐analysis of the RAFT trial (after excluding patients with ventricular pacing and permanent atrial fibrillation) showed that regardless the QRS duration, patients with LBBB morphology who were randomized to CRT with defibrillator function showed a reduction in the rates of the primary outcome (composite endpoint of all‐cause mortality and heart failure hospitalization) (HR 0.640; 95% CI 0.524–0.781; P  < 0.001) 5.…”
Section: Discussionmentioning
confidence: 99%
“…Recent meta-analysis of CRT studies has shown that baseline QRS duration . 150 ms was one of the best predictors of response to CRT (22)(23)(24)(25). Baseline LBBB morphology is associated with significant improvement in HF events, ventricular tachyarrhythmia, and death (23)(24)(25)(26).…”
Section: Comparison With Ecgmentioning
confidence: 98%
“…QRS duration and morphology have been shown to be predictors of response to CRT (22)(23)(24)(25). The Cardiac Resynchronization in Heart Failure study showed mortality benefit with CRT pacing alone in patients with LBBB morphology and QRS duration .…”
Section: Comparison With Ecgmentioning
confidence: 99%
See 2 more Smart Citations